2005
DOI: 10.1176/appi.ajp.162.3.530
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Depressive Reactions Among Children and Adolescents After the 1999 Earthquake in Ano Liosia, Greece

Abstract: This study demonstrated the feasibility of conducting large-scale school-based postdisaster mental health screening for planning intervention strategies. The present findings regarding PTSD and depression indicate the need to provide targeted specialized postdisaster mental health services to subgroups with significant levels of posttraumatic stress and depressive reactions after an earthquake of moderate intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
231
3
16

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(274 citation statements)
references
References 21 publications
24
231
3
16
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) is often considered as the most frequently reported adverse psychological sequelae among child and adolescent earthquake survivors [2][3][4][5][6]. For example, Giannopoulou et al [7] found that the prevalence rate of PTSD 6-7 months after the 1999 Athens earthquake was 35.7 % among youths aged 9-17 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttraumatic stress disorder (PTSD) is often considered as the most frequently reported adverse psychological sequelae among child and adolescent earthquake survivors [2][3][4][5][6]. For example, Giannopoulou et al [7] found that the prevalence rate of PTSD 6-7 months after the 1999 Athens earthquake was 35.7 % among youths aged 9-17 years.…”
Section: Introductionmentioning
confidence: 99%
“…Even more important than objective elements of traumatic events were individual's subjective experiences (e.g., the perception of threat and fear) in determining posttraumatic response [32]. For example, Roussos et al [5] examined the impact of both objective and subjective factors on PTSD symptoms of schoolchildren, and found that perceived threat to safety explained more variance in PTSD symptoms than objective measures of trauma severity, such as injury, the severity of house damage, or proximity to the epicenter.…”
Section: Introductionmentioning
confidence: 99%
“…The 1999 Athens earthquake is the most studied natural disaster in Greece in terms of the psychosocial effects on children, adolescents and adults (Giannopoulou et al, 2006; Goenjian et al, 2011; Groom & Soureti, 2004; Kolaitis et al, 2003; Roussos et al, 2005). This was a 5.9 Richter earthquake followed by 4000 aftershocks, had its epicentre in the north-western outskirts of Athens and was the most devastating in last 50 years, as it resulted in 143 deaths, more than 400 injuries and damage to 74,067 households.…”
Section: Current Research In Greecementioning
confidence: 99%
“…Ekşi et al (2007) reported that 60% of children and adolescents met PTSD criteria, and 31% had major depression following the earthquake in Turkey (Ekşi et al 2007). Several other studies conducted in China (Liu et al 2011), Armenia , and Greece (Groome and Soureti 2004;Roussos et al 2005) have similarly reported high anxiety and depression among adolescents who were exposed to earthquakes.…”
Section: Introductionmentioning
confidence: 97%